Emotion Regulation Strategies in Depression and Somatization Disorder. Issue 6 (December 2019) - Davoodi, Elham; Wen, Alainna; Dobson, Keith S.; Noorbala, Ahmad A.; Mohammadi, Abolfazl; Farahmand, Zahra
Scant research has investigated emotion regulation strategies in somatization disorder, despite its high comorbidity with depression and the growing interest in this topic in depression. The present study investigated emotion regulation strategies in patients with major depression and somatization disorder using clinical samples to examine common vulnerability factors and to provide evidence for difficulties in emotion regulation as transdiagnostic factors in these disorders. Patients with major depressive disorder ( n = 30) and patients with somatization disorder ( n = 30) completed measures of putatively adaptive and maladaptive emotion regulation strategy use. Patients with somatization disorder showed higher scores on measures of regulatory strategies, as measured by the sum of adaptive strategies in the Cognitive Emotion Regulation Questionnaire as well as the following subscales: positive refocusing, positive reappraisal, and refocusing on a plan. After controlling for levels of current depression, the significant effects remained for positive refocusing. Depression symptom severity was significantly and negatively correlated with most adaptive strategies and positively correlated with most maladaptive strategies. The current results provide preliminary data for a similar pattern of adaptive and maladaptive emotion regulation strategies usage in these two disorders. The results also contribute to theories of psychopathology and our understanding of critical cognitive and emotional processes.